Implementasi, Kebijakan Publik Implementasi Pemeliharaan Dan Penilikan Jalan Kabupaten Di Dinas Pekerjaan Umum Bina Marga Kabupaten Malang - Hilmi Ainul Fajar; Hayat Hayat; Mohammad Mas'ud Said (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
The implementation of road maintenance and surveillance policies is useful for providing comfort to road users in accordance with the Regulation of the Minister of Public Works Number 13 of 2011 concerning Procedures for Road Maintenance and Surveillance. Efforts to implement the policy are to provide services in the form of repairs, prevention of road conditions so as not to cause problems. The purpose of this research is to find out the implementation of road maintenance and surveillance in accordance with the Regulation of the Minister of Public Works Number 13 of 2011 concerning Road Maintenance and Surveillance Procedures. The results show that the implementation of road maintenance policy in Malang District is hampered by the shortage of quantity and quality of human resources and financial resources. The lack of competent human resources and the lack of financial resources have an impact on the course of implementing road maintenance policies. From these obstacles, the results of road maintenance implementation are not as expected. On the other hand, the community considers that the government of the Malang Regency Bina Marga Public Works Office has provided and shown positive services and responses in the implementation of road maintenance in Malang Regency. Community support is also a motivation for the government in implementing road maintenance policies.